(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
Chain saw machines are used for cutting vertical or horizontal cuts in underground and surface exploitationof dimension stone. Chainsaw performance in quarrying dimension stone depends on the right choice of machine’soperational parameters, cutting elements as well as the conditions and methods of quarrying in the certain type of rock.The key operational parameters which the operator must arrange on a chain saw are chain speed and cart speedmovement, while the values of this parameters are based on manufacturer’s recommendations and/or the operatorexperience. The main objective of this paper is to analyze the relationship between the operational parameters, chaindesign and chainsaw performance. Based on previous research, despite the limited literature on chain saw performance,it can be concluded that chain saws do not operate with optimum operational parameters, and current chain designs arenot efficient enough. Influence of the cutting chain design on the chainsaw performance can be analyzed by laboratorytests using a linear cutting machine. Although previous researches provide specific guidelines to increase chainsawperformance, further research should be directed to determine the optimal arrangement and the number of tools in thecutting segment as well as to the influence of the cutting geometry on the force and cutting energy.It is also reported that insufficient efficiency of chainsaw machines is due the shallow depth of cuts taken by the cuttingtools. Chain saw performance can be increased with the increase of the depth of cutting tools or with the decrease ofchain speed respectively. Optimal chain speed cannot be determined solely on the basis of the specific energy since theoptimal speed also depends on the cutting force and the wear of cutting tools as well as on the amount of materialcreated during the cutting. Additional laboratory and field experiments should analyse the influence of the abovequantities on chain saw performance in order to determine optimum constructional and operational parameters.